Determination of flexibility of workers working time through Taguchi method approach - Suhaila Saidat; Ahmad Kadri Junoh; Wan Zuki Azman Wan Muhamad; Zainab Yahya (Universitas Ahmad Dahlan, 2020)
Human factor is one of the important elements in manufacturing world, despite their important role in improvement the production flow, they have been neglected while scheduling for many decades. In this paper the researchers taken the human factor throughout their job performance weightage into consideration while using job shop scheduling (JSS) for a factory of glass industry, in order to improving the workers' flexibility. In other hand, the researchers suggested a new sequence of workers' weightage by using Taguchi method, which present the best flexibility that workers can have, while decreasing the total time that the factory need to complete the whole production flow.